Customer Relationship Management In the Banking Industry: An Extensive Review of CRM in the Banking Industry (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This Article provides an overview of CRM through an extensive review of the  literature. The chapter starts with somebasic concepts about CRM and its importance for the banking industry. Some discussions based on the currentoperation of CRM in the banking industry of both developed and developingcountries i.e. UK and Pakistan are presented and the major problems associatedwith the current use of CRM are also highlighted in this chapter. Similarly,multiple contact channels that are mostly offered by banks are also discussed. Moreover, based on the views ofseveral researchers, the chapter presents a taxonomy of several CRM components(i.e. CRM software and packages) that are mostly used in different departmentsof an ideal CRM   enabled bank. These CRMcomponents are mostly used in four major operational areas of a bank i.e. (i)marketing, (ii) sales, (iii) service and support, and (iv) IT and IS.Furthermore, some well known vendors of CRM for banks i.e. SAP, Oracle’s SiebelSystems, and Salesforce are thoroughly discussed. Finally, the chapterprovides  the best practices of CRM insome of the renowned banks.